Aromatic compound glucopyranoside from new species Artocarpus thailandicus - Wanaree Boonkla (2018)
Problem statement: Many Artocarpus plants belonging to the family Moraceae are found in Thailand and have been used as Thai traditional medicines. These plants are known to produce a variety of phenolic glycoside. A. thailandicus is the new species and this prompted us to make further investigations on the occurrence of these types of compounds in the new Artocarpus species. Thus, continuation of our work has resulted in the isolation of two aromatic glycoside compounds from the ethyl acetate extract of the leaves and twigs of A. thailandicus. Approach: The A. thailandicus was selected and percolated with hexane and ethyl acetate. The ethyl acetate extract was purified and elucidated chemical structures. Moreover, the purified compounds were tested for anti-bacterial activity. Results: Two compounds, p-hydroxyphenyl-6-acetoxy-β-D-glucopyranoside (1) and phydroxyphenyl- β-D-glucopyranoside (2), were isolated from the leaves and twigs of A. thailandicus by means of chromatography. Structural elucidation was achieved by1H,13C and 2D-NMR, as well as mass spectral data. Conclusion: The results showed that the two aromatic compound glucopyranosides from A. thailandicus could be recorded as constituent in the new species. © 2011 science publications.